Circular product design maturity matrix: A guideline to evaluate new product development in light of the circular economy transition. (10th September 2022) - Aguiar, Marina Fernandes; Jugend, Daniel
Abstract: Many recent studies have highlighted the role of circular product design in the light of the transition to the circular economy. Nevertheless, the gradual incorporation of circular economy practices, methods, and tools still requires further investigation, mainly in terms of new product development, which is a key process for the adoption of the circular economy. The main innovation of this paper is its proposal of a maturity matrix for the gradual adoption of the circular economy in the new product development process. The development and proposition of this maturity matrix was based on a literature review, evaluation from experts, and application in four companies, from different industrial sectors. The matrix is composed of five maturity levels and eleven analysis dimensions, encompassing the circular economy-oriented design strategies. Among the main outcomes, the application of the matrix provides a diagnosis and broader understanding of how circular the new product development process in a company is. Moreover, the matrix can guide companies to gradually improve circular economy integration through the design of new products, contributing to the theoretical and managerial debate about the transformation processes involved in the transition from a linear to a circular economy. Highlights: The study identifies and systematizes current knowledge on circular product design (CPD). A maturity matrix integrating CPD strategies and management practices was developed and proposed. The paper discusses the results of the application of the matrix in four companies. The matrix provides a diagnosis of the maturity level and in-depth insights regarding CPD.